2019
DOI: 10.3390/cells8121488
|View full text |Cite
|
Sign up to set email alerts
|

pMHC Structural Comparisons as a Pivotal Element to Detect and Validate T-Cell Targets for Vaccine Development and Immunotherapy—A New Methodological Proposal

Abstract: The search for epitopes that will effectively trigger an immune response remains the “El Dorado” for immunologists. The development of promising immunotherapeutic approaches requires the appropriate targets to elicit a proper immune response. Considering the high degree of HLA/TCR diversity, as well as the heterogeneity of viral and tumor proteins, this number will invariably be higher than ideal to test. It is known that the recognition of a peptide-MHC (pMHC) by the T-cell receptor is performed entirely in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Hierarchical clustering analysis showed that four out of eight investigated alleles presented an electrostatic potential distribution fingerprint in the probed area. This physicochemical element was already described as pivotal to cytotoxicity elicitation, as described previously ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hierarchical clustering analysis showed that four out of eight investigated alleles presented an electrostatic potential distribution fingerprint in the probed area. This physicochemical element was already described as pivotal to cytotoxicity elicitation, as described previously ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…All the recovered epitopes for Alpha and Beta Coronaviruses and analysed VOCs were modeled in HLA-A*02:01 context to investigate their TCR interaction surfaces looking for immunogenicity fingerprints and shared structural features. The full applied rationale can be found in ( 53 ). The Docktope tool ( ) allowed to produce pMHC models containing the analysed peptides anchored to the HLA-A*02:01 Class I MHC (pMHC).…”
Section: Methods and Resourcesmentioning
confidence: 99%